SDHC methylation in gastrointestinal stromal tumors (GIST): a case report. Issue 1 (December 2015) - Urbini, Milena; Astolfi, Annalisa; Indio, Valentina; Heinrich, Michael; Corless, Christopher; Nannini, Margherita; Ravegnini, Gloria; Biasco, Guido; Pantaleo, Maria
Abstract Background Gastrointestinal stromal tumors (GIST) recently have been recognized as a genetically and biologically heterogeneous disease. In addition toKIT orPDGFRA mutated GIST, mutational inactivation of succinate dehydrogenase (SDH) subunits has been detected in theKIT /PDGFRA wild-type subgroup, referred to as SDH deficient (dSDH). Even though most dSDH GIST harbor mutations in SDHx subunit genes, some are SDHx wild type. Epigenetic regulation by DNA methylation of CpG islands recently has been found to be an alternative mechanism underlying the lack of SDH complex in GIST. Case presentation We report a particular case of dSDH GIST, previously analyzed with microarrays and next-generation sequencing, for which no molecular pathogenetic events have been identified. Gene expression analysis showed remarkable down-modulation ofSDHC mRNA with respect to all other GIST samples, bothSDHA -mutant andKIT /PDGFRA -mutant GIST. By a bisulfite methylation assay targeted to 2SDHC CpG islands, we detected hypermethylation of theSDHC promoter. Conclusion Herein we report an additional case of dSDH GIST without SDHx mutation but harboring hypermethylation in theSDHC promoter, thus confirming the complexity of the molecular background of this subtype of GIST.